2022
DOI: 10.26552/com.c.2022.4.b310-b318
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of Maximum Stresses in the Stationary Hoist Design in the Ansys Software Environment

Abstract: The authors have studied the methods of loading bulk cargo in the railway transport. The developed method of loading bulk cargoes into containers transported by railway platforms has been developed. The article deals with experimental studies of maximum stresses in the design of the proposed stationary hoist. The studies have been carried out in the ANSYS software environment with development of simulation models of the hoist design.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…The maximum use of the internal volume of the warehouse and the optimal placement of racks contribute to increasing efficiency and saving resources when storing and moving goods in the warehouse. The optimal placement of racks in the warehouse has its advantages in terms of capacity, however, such a traditional layout is also associated with some disadvantages, including an increase in operating costs associated with the movement of loading and unloading equipment from the loading and unloading area to the cargo storage areas [1][2][3][4].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The maximum use of the internal volume of the warehouse and the optimal placement of racks contribute to increasing efficiency and saving resources when storing and moving goods in the warehouse. The optimal placement of racks in the warehouse has its advantages in terms of capacity, however, such a traditional layout is also associated with some disadvantages, including an increase in operating costs associated with the movement of loading and unloading equipment from the loading and unloading area to the cargo storage areas [1][2][3][4].…”
Section: Methodsmentioning
confidence: 99%
“…The transformation of cargo flows and the efficiency of warehouses in the cargo transshipment zone between different modes of transport play an important role in the technological scheme of cargo delivery. Optimal equipment and organization of intermediate warehouses in transport significantly affect the effectiveness of this scheme [1][2][3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Turanov and other recognized scientists to determine the height of the sorting slide, it is calculated based on the most difficult conditions -winter temperature and headwind, and for a bad runner, a four-axle empty covered wagon is selected. The reason for choosing this car was that the cross-sectional area of the closed car is larger than that of other cars (Table 1) [4,6,8,10,12,14,16,18]. The following forces act on a car moving along an inclined plane (Fig.…”
Section: The Main Partmentioning
confidence: 99%
“…Analyzing the content of the published discussions devoted to the problem of designing sorting slides [1][2][3][4][5][6][7][8][9][10], it can be concluded that until now the dynamics of the car moving along the profile of the sorting slide has not been studied enough. For this reason, it is worth noting the ideas about the importance of controlling, coordinating the speed of a moving car along the profile of a sorting slide.…”
Section: Introductionmentioning
confidence: 99%
“…To the approach of vehicles to the warehouse. In this regard, the task of describing this process arises [1][2][3][4][5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%